EARNING MANAGEMENT TERHADAP NILAI PERUSAHAAN UNTUK KOMISARIS INDEPENDEN DAN KOMITE AUDIT SEBAGAI VARIABEL PEMODERASI - Widyaningsih, Ika Utami (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to find out how earnings management practices influence company value, with independent commissioners and audit committees as moderating variables. This research uses a sample of manufacturing companies that have complete data on the variables studied in the manufacturing sector in 2022. The data analysis method used is moderated regression analysis. The research results show that earnings management has a negative and significant influence on company value. Apart from that, independent commissioners and audit committees have been proven to be able to moderate the influence of earnings management on company value. These findings indicate that the presence of independent commissioners and audit committees can strengthen supervision of earnings management practices, thereby increasing company value. Therefore, the results of this research have important implications for corporate governance policies and the importance of strengthening the role of independent commissioners and audit committees in companies